Organosilicon polymer as well as preparation method and application thereof

By introducing branched structures and cyclic structures into the main chain of silicone polymers and controlling the content of unsaturated groups, the problems of low ceramic yield and high residual carbon content are solved, and the effects of high molecular weight and high ceramic yield are achieved.

CN119661852APending Publication Date: 2025-03-21QIANWAN INST OF CNITECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311204971.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

It is difficult to obtain silicone polymers with high ceramic yield and low residual carbon content in the prior art, and their molecular weight and stability are insufficient.

Method used

By introducing branched structures and cyclic structures into the main chain of silicone polymers, and controlling the content of unsaturated groups on the Si atoms, the molecular weight and reaction yield are improved, and the residual carbon content is reduced.

Benefits of technology

The high molecular weight of silicone polymers, the improvement of ceramic yield and the reduction of residual carbon content are achieved, while the storage stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661852A_ABST
    Figure CN119661852A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of SiC ceramics, and relates to a SiC ceramic raw material organosilicon polymer, a preparation method thereof and an application of the SiC ceramic raw material organosilicon polymer converted into SiC ceramics. The organic silicon polymer has a main chain formed by alternately connecting Si atoms and C atoms, and the main chain comprises a branched structure and / or a cyclic structure; the main chain has a composition structure that # imgabs0 # and # imgabs1 # and / or # imgabs2 # Si atoms are independently connected with one or more of H, alkyl, aryl, substituted aryl and unsaturated groups to form sp3 hybridization. The introduction of the structure # imgabs3 # and / or # imgabs4 # is beneficial to improving the molecular weight of the organosilicon polymer and reducing the content of unsaturated groups, and can also achieve the effects of improving the reaction yield, reducing the content of residual C, improving the ceramic yield and reducing the proportion of-SiH3 groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of SiC ceramics, and relates to organic silicon polymer, a raw material of SiC ceramics, a preparation method thereof, and application of converting it into SiC ceramics. Background Art

[0002] Organic silicon polymers with -Si-C- as the main chain and H, alkyl, aryl or unsaturated groups connected to Si and C atoms can be converted into SiC ceramics in different forms by high-temperature pyrolysis. SiC ceramics have excellent properties such as high hardness, high thermal conductivity, low creep, corrosion resistance, radiation resistance, high temperature resistance and oxidation resistance. They are ideal high-safety structural materials in extreme environments such as high temperature, strong neutron irradiation, high-speed friction and strong corrosion. Therefore, this type of organic silicon polymer has important application value.

[0003] Grignard coupling is an important method for preparing this type of organosilicon polymer. 3 SiC 2 Cl (also written as ClCH 2 SiCl 3 ) as a raw material, magnesium can effectively recognize the Si-Cl bond and C-Cl bond in its structure, selectively react only with C-Cl to form a Grignard reagent, and the Grignard reagent couples with Si-Cl to form a chlorinated organosilicon polymer intermediate, which is then reduced to obtain the organosilicon polymer (Ackley BJ, Martin KL, Key TS, et al. Advances in the synthesis of preceramic polymers for the formation of silicon-based and ultrahigh-temperature non-oxide ceramics. Chem. Rev. 2023, 123, 4188-4236), which has a relatively complex structure, including a branched structure and a ring structure.

[0004] But due to Cl 3 SiC 2 The Si-Cl group in the Cl monomer is easily substituted with ether solvents, and the ether solvents are introduced into the organosilicon polymer through chemical bonds, resulting in problems such as high oxygen content in the ceramic product. The current solution is to replace Cl 3 SiC 2 The Si-Cl group in Cl is partially alkylated or alkoxylated.

[0005] For an ideal organosilicon polymer, it is required not only to have a low oxygen content but also a high ceramic yield. For this reason, some unsaturated groups that can cause cross-linking are also introduced (including allyl, vinyl, ethynyl, acrylate, etc.). Cross-linking can reduce the volatility of low molecular weight organosilicon polymers, but the introduction of unsaturated groups will also bring some negative effects, such as an increase in residual carbon content, and too high unsaturated group content will also lead to a decrease in ceramic yield. For example, in the literature (He LJ, Zhang ZB, Yang XG, Jiao LL, Li YM, Xu CH. Liquid polycarbosilanes: synthesis and evaluation as precursors for SiC ceramic. Polym. Int., 2015, 64 (8): 979-985.), chloromethyl trimethoxy silane and vinyl magnesium chloride are used as raw materials to synthesize organosilicon polymers. When the molar ratio of chloromethyl trimethoxy silane to vinyl magnesium chloride is increased from 6 / 1 to 1 / 6, the 1000°C ceramic yield gradually decreases from 63.8 wt% to 33.6 wt%; the C / Si ratio of the ceramic product increases from 1.48 to 3.46. Therefore, how to obtain an organosilicon polymer with high ceramic yield and low residual carbon content is a technical difficulty in this field. Summary of the invention

[0006] The object of the present invention is to provide an organosilicon polymer with the advantages of high molecular weight, high ceramic yield and low residual carbon content in view of the deficiencies of the prior art. The present invention also provides a method for preparing the organosilicon polymer, and the organosilicon polymer obtained by the preparation method has a high yield. Furthermore, the present invention also provides the application of the organosilicon polymer.

[0007] The first object of the present invention is achieved by the following technical solutions:

[0008] An organic silicon polymer having a main chain formed by alternating Si atoms and C atoms, wherein the main chain includes a branched structure; the composition structure of the main chain includes as well as and / or Si atom is independently connected to one or more selected from H, alkyl, aryl, substituted aryl, unsaturated group to form sp 3 Hybridization.

[0009] Optionally, the main chain of the organosilicon polymer of the present invention may also include a ring structure.

[0010] The main chain structure includes as well as and / or Right now and / or Random or ordered connections form the main chain.

[0011] The principle of designing organic silicon polymer in the present invention is: in conventional Introduced into the main chain structure and / or The molecular weight of the organosilicon polymer is increased by connecting structures such as the above, and the increase in molecular weight is conducive to ensuring cross-linking and curing under the condition of appropriately reducing the content of unsaturated groups. Therefore, the organosilicon polymer of the present invention has the advantages of high molecular weight and no / low unsaturated group content, and can also achieve the effects of increasing reaction yield, increasing ceramic yield, reducing residual carbon content and improving stability.

[0012] structure and Can be used with structure Existing in the main chain of the organic silicon polymer, at this time, the molar ratio of each structure to the three structures is between 1% and 90%, but the sum of the molar ratios of the three structures is 100%; structure and Can also be separated from the structure Existing in the main chain of the organic silicon polymer. The introduction of has a more significant effect on increasing the molecular weight and the reaction yield.

[0013] Therefore, as a preference, the organosilicon polymer provided by the present invention has a main chain formed by alternating Si atoms and C atoms, wherein the main chain includes a branched structure and / or a ring structure; the composition structure of the main chain includes and Not included Si atom is independently connected to one or more selected from H, alkyl, aryl, substituted aryl, unsaturated group to form sp 3 Hybridization.

[0014] In addition to forming a bond with a C atom, the Si atom in the above structure is also independently connected to one or more selected from H, alkyl, aryl, substituted aryl, and unsaturated groups to form a sp 3 Hybridization.

[0015] Optionally, the alkyl group attached to the Si atom is C 1 ~C 18 The alkyl group may be one or more of a linear alkyl group, a branched alkyl group, and a cyclic alkyl group. 1 ~C 12 Alkyl; Optionally, the alkyl group attached to the Si atom is C 1 ~C 6 alkyl.

[0016] Optionally, the aryl group attached to the Si atom is C 6 ~C 24 Further, the aryl group is C 6 ~C 18 Further, the aryl group is C 6 ~C 12 Aryl.

[0017] The substituted aryl group attached to the Si atom is a substituted aryl group in which any hydrogen atom on the aromatic ring of the aryl group is independently replaced by any C 1 ~C 18 of alkyl substitution.

[0018] Optionally, the unsaturated group connected to the Si atom is an unsaturated group containing C═C and / or C≡C.

[0019] Examples of the unsaturated group containing C═C and / or C≡C include alkenyl, alkynyl, acrylate, alkenyl ether, alkynyl ether and the like.

[0020] However, the introduction of alkyl and unsaturated groups on Si atoms will lead to an increase in the C / Si ratio in the organosilicon polymer, which is not conducive to improving the ceramic yield and the performance of the converted SiC ceramics and SiC ceramic-based composite materials.

[0021] Preferably, the Si atom is independently connected to one or more selected from H, unsaturated groups to form sp 3 Hybridization. Moreover, the content of unsaturated groups connected to Si atoms needs to be controlled. Therefore, as a further preferred embodiment, the molar ratio of Si atoms connected to unsaturated groups to total Si atoms is 0.01 to 0.2. A more preferred embodiment is that the molar ratio of Si atoms connected to unsaturated groups to total Si atoms is 0.01 to 0.1.

[0022] Structure in the main chain and The content needs to be controlled, too high and The content of 2-hydroxy-2-nitropropene will result in the molecular weight of the obtained organosilicon polymer being too high, and even cross-linking into an insoluble and infusible solid, which loses fluidity, thereby reducing the reaction yield of the organosilicon polymer. and When there are two structures, The molar amount of the two structures accounts for 1% to 60% of the total molar amount of the two structures. More preferably, the structure The molar amount of these two structures accounts for 10% to 50% of the total molar amount; when the organosilicon polymer contains and Three structures, structure and The molar amount of the three structures accounts for 1% to 60% of the total molar amount of the three structures. and The molar amount of the three structures accounts for 10% to 50% of the total molar amount; when the organosilicon polymer contains and When there are two structures, The molar amount of the two structures accounts for 1% to 50% of the total molar amount of the two structures. More preferably, the structure The molar amount of the two structures accounts for 10% to 40% of the total molar amount.

[0023] The second object of the present invention is achieved by the following technical solutions:

[0024] A method for preparing an organosilicon polymer comprises the following steps:

[0025] by and / or as well as As a monomer, an organosilicon polymer is obtained through a Grignard reaction step and a reduction reaction step, wherein X is selected from one or more halogen groups; R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9 is independently selected from one or more of H, halogen, alkyl, alkoxy, aryl, substituted aryl, and unsaturated groups; R 1 , R 2 and R 3 At least one of them is a halogen group or an alkoxy group.

[0026] The above-mentioned alkyl, aryl, substituted aryl, and unsaturated groups refer to the relevant introduction of the organosilicon polymer provided in the first object of the present invention. Optionally, the alkoxy group is C 1 ~C 18 The alkoxy group may be a straight chain or a branched chain; further, the alkoxy group is C 1 ~C 12 Alkoxy; further, the alkoxy is C 1 ~C 6 Alkoxy; most preferably, the alkoxy is methoxy. The halo is F, Cl, Br or I.

[0027] In order to reduce the residual carbon content, R 1 , R 2 , R 3 , R 4 , R 5, R 6 , R 7 , R 8 The structure does not contain alkyl, aryl, or substituted aryl. 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9 is independently selected from one or more of H, halogen, alkoxy, and unsaturated groups; R 1 , R 2 and R 3 At least one of them is a halogen group or an alkoxy group.

[0028] In the preparation method of the present invention, if As a monomer, after the Grignard reaction step and the reduction reaction step, a and Silicone polymer; As a monomer, after the Grignard reaction step and the reduction reaction step, a and Silicone polymer; As a monomer, after the Grignard reaction step and the reduction reaction step, a and Silicone polymer.

[0029] In the above preparation method, preferably, the Grignard reaction step comprises: monomer and / or And monomer Magnesium metal undergoes a Grignard reaction in an ether solvent to obtain an intermediate of an organosilicon polymer.

[0030] Preferably, the Grignard reaction step specifically comprises: monomer as well as and / or Add magnesium metal to an ether solvent, or add magnesium metal to a monomer as well as and / or A Grignard reaction is carried out in an ether solvent to obtain an intermediate of an organosilicon polymer.

[0031] The study found that the monomer that plays a cross-linking role and / or In monomer Adding after the reaction is more conducive to increasing the molecular weight of the organosilicon polymer. Therefore, it is further preferred that in the Grignard reaction step, the monomer and / or The feeding time is later than The Grignard reaction step specifically includes: monomer Add to the ether solvent containing magnesium metal, and after the feeding is completed, add and / or The Grignard reaction is carried out to obtain an intermediate of an organosilicon polymer.

[0032] Preferably, during the feeding process, the temperature is controlled at 40-70°C.

[0033] Preferably, the Grignard reaction is carried out at 45-85° C. for 1-50 h; more preferably, the Grignard reaction is carried out at 50-80° C. for 5-40 h; more preferably, the Grignard reaction is carried out at 60-80° C. for 8-30 h.

[0034] The present invention has found that compared with monomer monomer Since it contains more CX groups, it is more conducive to increasing the molecular weight of the organosilicon polymer and can also reduce the use of expensive reducing agents. Therefore, as a preferred method, the preparation method of the organosilicon polymer includes the following steps: As a monomer, an organosilicon polymer is obtained through a Grignard reaction step and a reduction reaction step, wherein X is selected from one or more halogen groups; R 1 , R 2 , R 3 , R 7 , R 8 and R 9 is independently selected from one or more of H, halogen, alkyl, alkoxy, aryl, substituted aryl, and unsaturated groups; R 1 , R 2 and R 3 At least one of them is a halogen or an alkoxy group. The Grignard reaction steps at this time include: monomer monomer Magnesium metal undergoes a Grignard reaction in an ether solvent to obtain an intermediate of an organosilicon polymer.

[0035] Cross-linking groups are beneficial to the curing and molding of organic silicon polymers and the improvement of ceramic yield. In addition, the cross-linkable unsaturated groups can be introduced into the organosilicon polymer by adding unsaturated halogenated hydrocarbons and / or Grignard reagents in the Grignard reaction step. In this case, the Grignard reaction step includes: monomers and / or And monomer Magnesium metal, unsaturated halogenated hydrocarbons and / or their Grignard reagents undergo Grignard reaction in an ether solvent to obtain an intermediate of an organosilicon polymer. Preferably, the unsaturated halogenated hydrocarbons include CX groups, C=C groups and / or C≡C groups, wherein X is a halogen element. Further preferably, the unsaturated halogenated hydrocarbons are alkenes or alkynes containing CX groups. The unsaturated halogenated hydrocarbons can be listed as one or more of vinyl bromide, vinyl chloride, allyl chloride, allyl bromide, propargyl chloride, propargyl bromide, ethynyl bromide, and ethynyl chloride. The Grignard reagents of the unsaturated halogenated hydrocarbons can be listed as one or more of allyl magnesium chloride, vinyl magnesium bromide, vinyl magnesium chloride, propargyl magnesium chloride, ethynyl magnesium bromide, propargyl magnesium bromide, ethynyl magnesium chloride, and allyl magnesium bromide.

[0036] The number of unsaturated groups in the organosilicon polymer needs to be controlled and cannot be too high. Therefore, as a preference, the molar amount of the unsaturated halogenated hydrocarbon and / or its Grignard reagent is 0.005 to 0.2 of the total molar amount of the monomer; further, the molar amount of the unsaturated halogenated hydrocarbon and / or its Grignard reagent is 0.005 to 0.1 of the total molar amount of the monomer.

[0037] In the above-mentioned method for preparing organosilicon polymer, when comprising When there are three monomers, the molar ratio of each monomer to the three monomers is between 1% and 90%, but the sum of the molar ratios of the three monomers is 100%. When there are two monomers, The molar amount of the two monomers accounts for 1% to 60% of the total molar amount of the two monomers. More preferably, the monomer The molar amount of the two monomers accounts for 10% to 50% of the total molar amount; when it contains When there are three monomers, The molar amount of the three monomers accounts for 1% to 60% of the total molar amount of the three monomers. More preferably, the monomer The molar amount of the three monomers accounts for 10% to 50% of the total molar amount; when it contains When there are two monomers, The molar amount of the two monomers accounts for 1% to 50% of the total molar amount of the two monomers. More preferably, the monomer The molar amount of the two monomers accounts for 10% to 40% of the total molar amount of the two monomers.

[0038] Magnesium metal is used to form a Grignard reagent with CX. Preferably, the molar amount of magnesium metal is ≥ the total molar amount of all CX groups. More preferably, the molar amount of magnesium metal is 1.01 to 1.8 times the total molar amount of all CX groups. The CX groups mentioned here include not only monomers The CX group in the alkylene oxide also includes the CX group in the unsaturated halogenated hydrocarbon.

[0039] Optionally, the ether solvent is selected from one of tetrahydrofuran, 2-methyltetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, methyl tert-amyl ether, cyclopentyl methyl ether, etc., or a mixture of two or more thereof.

[0040] In the above-mentioned method for preparing organosilicon polymer, preferably, the reduction reaction step comprises: adding a reducing agent to the product of the Grignard reaction to carry out a reduction reaction.

[0041] The reducing agent may be any effective reducing agent capable of reducing the halogen and / or alkoxy groups on the intermediate of the organosilicon polymer to H, including but not limited to LiAlH 4 、NaAlH 4 , red aluminum, NaBH 4 The reducing agent may be added in the form of solid powder or particles, or in the form of a solution dissolved or dispersed in a solvent.

[0042] Preferably, the reduction reaction is carried out at 45-85° C. for 1-40 h; more preferably, the reduction reaction is carried out at 50-80° C. for 2-30 h; more preferably, the reduction reaction is carried out at 60-80° C. for 2-20 h.

[0043] The principle followed by the amount of the reducing agent added is that the molar amount of the effective reduced hydrogen in the reducing agent is greater than or equal to the molar amount of the halogen group and the alkoxy group in the intermediate structure of the organic silicon polymer.

[0044] In the above-mentioned preparation method of the organosilicon polymer, preferably, after the Grignard reaction step and the reduction reaction step, an extraction and concentration step is further performed. The extraction and concentration step comprises: mixing the reduction reaction product with an acidic aqueous solution, extracting with an organic extractant, concentrating the organic phase obtained by extraction to remove the organic extractant, and obtaining the organosilicon polymer.

[0045] The reduction reaction product is mixed with an acidic aqueous solution, and the mixing is preferably carried out below zero degrees Celsius. The acidic aqueous solution can be a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a phosphoric acid aqueous solution, a nitric acid aqueous solution, etc., and the concentration of the acidic aqueous solution can be listed as 1 to 10 mol / L. After the mixed solution of the reduction reaction product and the acidic aqueous solution is extracted with an organic extractant, an organic phase containing the organosilicon polymer and an aqueous solution containing an inorganic magnesium salt, lithium salt, sodium salt or aluminum salt can be obtained, and the organic phase and the aqueous solution are separated after liquid separation. The organic extractant can be selected from a low-boiling point solvent that is difficult to dissolve in water but can dissolve the organosilicon polymer, such as petroleum ether, ether, halogenated hydrocarbons, hexane, heptane, octane, benzene, toluene.

[0046] The third object of the present invention is achieved by the following technical solutions:

[0047] An application of an organosilicon polymer, the application comprising one or more of the following:

[0048] a. Applied in the preparation of SiC ceramic matrix composite materials, porous SiC ceramics or SiC fibers,

[0049] b. Preparation of protective coatings for carbon materials, metals, ceramics or ceramic-based composite materials,

[0050] c. Applied to filling and / or strengthening of carbon materials, metals, ceramics or ceramic matrix composites,

[0051] d. Applied to the connection of ceramics or ceramic matrix composite materials,

[0052] e. Applied to the forming of complex SiC ceramic components.

[0053] Compared with the prior art, the present invention is Introduced into the main chain structure of organic silicon polymer and / or The structure has the following beneficial effects:

[0054] (1) It is conducive to obtaining high molecular weight silicone polymers;

[0055] (2) The increase in the molecular weight of the organosilicon polymer is conducive to reducing the content of carbon-rich unsaturated groups, thereby reducing the residual carbon in the converted SiC ceramics;

[0056] (3) It is beneficial to improve the storage stability of silicone polymers;

[0057] (4) Compared with monomer monomer The introduction of has a more significant effect in increasing the molecular weight of silicone polymers, reducing the content of cross-linking groups and C / Si.

[0058] (5) The method for preparing the organosilicon polymer of the present invention has a higher reaction yield;

[0059] (6) The organosilicon polymer of the present invention has a higher ceramic yield;

[0060] (7) The structural modification of the organic silicon polymer does not affect the application of the organic silicon polymer converted into silicon carbide ceramics by high-temperature pyrolysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is the H-NMR spectrum of the organosilicon polymer described in Comparative Example 1 of the present invention;

[0062] Figure 2 is the H-NMR spectrum of the organosilicon polymer described in Example 1 of the present invention;

[0063] Figure 3 is the XRD pattern of the organosilicon polymer described in Example 4 of the present invention;

[0064] Figure 4 This is the SEM spectrum of the carbon fiber with SiC protective coating on the surface prepared in Example 18 of the present invention. DETAILED DESCRIPTION

[0065] The technical solution of the present invention is further described below through specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not used to specifically limit the present invention. The drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection.

[0066] The performance tests in the following comparative examples and embodiments were carried out using the following instruments:

[0067] NMR: Tested using Bruker AvanceⅢ NMR instrument from Bruker, Germany;

[0068] Molecular weight: tested by HLC-8320GPC gel permeation chromatograph from TOSOH, Japan;

[0069] Oxygen content: tested using EMGA-620 oxygen and nitrogen analyzer from Japan HORIBA Company;

[0070] Thermal weight loss: tested using TG-DTA 6300 thermogravimetric analyzer produced by Seiko of Japan;

[0071] X-ray diffraction: The test was conducted using a Bruker D8 Advance multi-crystal X-ray diffractometer from Bruker, Germany.

[0072] Three-point bending strength: tested using German Zwick 30KN material testing machine.

[0073] Comparative Example 1

[0074] Add ClCH in one go to a 1000 mL two-necked flask with a dropping funnel and a gas tube. 2 SiCl 3 (368 g), then CH 3 OH (112 g), and then continue to react at room temperature for 2 h. The HCl produced by the reaction is absorbed and neutralized by a NaOH aqueous solution to obtain ClCH 2 SiCl 1.25 (CH 3 O)1.75 (is ClCH 2 SiCl 2 (CH 3 O), ClCH 2 SiCl(CH 3 O) 2 With ClCH 2 Si(CH 3 O) 3 The molar ratio of the three components in the formed mixture was estimated by NMR to be approximately 0.36:0.53:0.11).

[0075] Under nitrogen protection, magnesium metal (18.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 1.25 (CH 3 O) 1.75 (88g) and propylene chloride (3.8g). After the addition of the materials, the reaction was kept at 65℃ for 12h. Then the temperature was lowered to room temperature and LiAlH 4 (11.7 g) and kept at 65°C for 12 h.

[0076] The reaction solution was mixed with HCl aqueous solution (330 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the organic silicon polymer synthesized by the reaction. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value of -0.093 to -0.096MPa) gave 16.3g of liquid organosilicon polymer, with a reaction yield of 67.9%. Gel permeation chromatography analysis showed that the number average molecular weight was 783 and the weight average molecular weight was 1703. The NMR spectrum is shown in the attached figure. Figure 1 As shown, where -SiH 3 Structure in all-SiH x The proportion in the solution is 30%. Take 0.5 mL and evenly apply it on a glass slide with a size of 25*75 mm, place it in a 35℃ constant temperature box, and gel after 25 hours.

[0077] The obtained liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 75.2%. Elemental analysis showed that the C content was 33.09wt%, the O content was 1.53wt%, and the Si content was 65.38wt% by subtraction method, and the C / Si ratio was 1.18.

[0078] Comparative Example 2

[0079] Add ClCH in one go to a 1000 mL two-necked flask with a dropping funnel and a gas tube. 2 SiCl 3 (368 g), then CH 3 OH (144 g), and then continue to react at room temperature for 2 h. The HCl produced by the reaction is absorbed and neutralized by a NaOH aqueous solution to obtain ClCH 2 SiCl 0.75 (CH 3 O) 2.25 (is ClCH 2 SiCl 2 (CH 3 O), ClCH 2 SiCl(CH 3 O) 2 With ClCH 2 Si(CH 3 O) 3 The molar ratio of the three components in the formed mixture was estimated by NMR to be approximately 0.13:0.49:0.38).

[0080] Under nitrogen protection, magnesium metal (18.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 0.75 (CH 3 O) 2.25 (87g) and vinyl bromide (5.4g). After the addition of the materials, the reaction was carried out at 65℃ for 15h. Then the temperature was lowered to room temperature and LiAlH 4 (11.7 g) and kept at 65°C for 12 h.

[0081] The reaction solution was mixed with HCl aqueous solution (330 mL, concentration 4 mol / L) at 0°C, and ether (360 mL) was added to extract the organic silicon polymer synthesized by the reaction. 2 SO 4 After drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value of -0.093 to -0.096MPa), 15.4g of liquid organosilicon polymer was obtained, and the reaction yield was 66.1%. According to gel permeation chromatography analysis, the number average molecular weight was 842 and the weight average molecular weight was 1824.

[0082] Liquid organosilicon polymer (2 g) was mixed with dibenzoyl peroxide (0.02 g) and then cured at 120°C for 1 hour in a nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 78.2%. Elemental analysis showed that the C content was 32.49 wt%, the O content was 1.37 wt%, and the Si content was 66.14 wt% by subtraction method, and the C / Si ratio was 1.15.

[0083] Comparative Example 3

[0084] Under nitrogen protection, magnesium metal (18.4 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, the ClCH synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (88g) and propylene chloride (3.1g). After the addition of the materials, the reaction was carried out at 65℃ for 12h. Then the temperature was lowered to room temperature and LiAlH 4 (11.9 g) and kept reacting at 65°C for 12 h.

[0085] The reaction solution was mixed with HCl aqueous solution (325 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 After drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value of -0.093 to -0.096MPa), 15.7g of liquid organosilicon polymer was obtained, with a reaction yield of 66.5%. According to gel permeation chromatography analysis, the number average molecular weight was 764 and the weight average molecular weight was 1732.

[0086] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 73.2%. Elemental analysis showed that the C content was 32.38 wt%, the O content was 1.81 wt%, and the Si content was 65.81 wt% by subtraction method, and the C / Si ratio was 1.15.

[0087] Comparative Example 4

[0088] Under nitrogen protection, magnesium metal (17 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, the ClCH synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 2SiCl 1.25 (CH 3 O) 1.75 (88g). After the feeding was completed, the reaction was kept at 65°C for 12h. Then the temperature was lowered to room temperature and LiAlH 4 (12.4 g) and kept at 65°C for 12 h.

[0089] The reaction solution was mixed with HCl aqueous solution (310 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 After drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge reading -0.093 to -0.096 MPa), 14.1 g of liquid organosilicon polymer was obtained with a reaction yield of 64%. According to gel permeation chromatography analysis, the number average molecular weight was 730 and the weight average molecular weight was 1639.

[0090] Due to the absence of unsaturated groups, the mass retention rate was only 43.6% when the temperature was increased from 10°C / min to 1000°C in a thermogravimetric analyzer. Elemental analysis showed that the C content was 29.75wt%, the O content was 1.53wt%, and the Si content was 68.72wt% by subtraction method, with a C / Si ratio of 1.01.

[0091] Example 1

[0092] Add Cl in one go to a 1000 mL two-necked flask with a dropping funnel and a gas tube. 3 CSiCl 3 (506 g), then CH 3 OH (112 g), then react at room temperature for 2 h, the HCl produced by the reaction was absorbed and neutralized by NaOH aqueous solution to obtain Cl 3 CSiCl 1.25 (CH 3 O) 1.75 (It is Cl 3 CSiCl 2 (CH 3 O), Cl 3 CSiCl(CH 3 O) 2 With Cl 3 CSi(CH 3 O) 3 The molar ratio of the three components in the formed mixture was estimated by nuclear magnetic resonance (NMR) to be approximately 0.34:0.57:0.09).

[0093] Under nitrogen protection, magnesium metal (25.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and the Cl synthesized in this example 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The temperature of the reaction solution was lowered to room temperature, and then LiAlH 4 (9.3 g), and reacted at 65 °C for 12 h.

[0094] The reaction solution was mixed with HCl aqueous solution (450 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value is -0.093 to -0.096MPa). 20.3g of liquid organosilicon polymer was obtained, and the reaction yield was 85.9%. According to gel permeation chromatography analysis, the number average molecular weight was 1836 and the weight average molecular weight was 7290. The NMR spectrum is as attached Figure 2 As shown, where -SiH 3 Structure in all-SiH x The proportion in the solution is 22%. Take 0.5 mL and evenly apply it on a glass slide with a size of 25*75 mm, place it in a 35℃ constant temperature box, and gel after 68 hours.

[0095] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 83.9%. Elemental analysis showed that the C content was 32.51 wt%, the O content was 1.71 wt%, and the Si content was 65.78 wt% by subtraction method, and the C / Si ratio was 1.15.

[0096] Example 2

[0097] Add Cl in one go to a 1000 mL two-necked flask with a dropping funnel and a gas tube. 3 CSiCl 3 (506 g), then CH 3OH (144 g), then reacted at room temperature for 2 h, the HCl produced by the reaction was absorbed and neutralized by NaOH aqueous solution to obtain Cl 3 CSiCl 0.75 (CH 3 O) 2.25 (It is Cl 3 CSiCl 2 (CH 3 O), Cl 3 CSiCl(CH 3 O) 2 With Cl 3 CSi(CH 3 O) 3 The molar ratio of the three components in the formed mixture was estimated by NMR to be approximately 0.11:0.53:0.36).

[0098] Under nitrogen protection, magnesium metal (22.1 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 2 was added in sequence through the dropping funnel. 2 SiCl 0.75 (CH 3 O) 2.25 (78.3 g) and the Cl synthesized in this example 3 CSiCl 0.75 (CH 3 O) 2.25 After the addition of the feed, the mixture was kept at 65°C for 15 h. Then the mixture was cooled to room temperature and LiAlH 4 (10.5 g) and kept at 65°C for 12 h.

[0099] The reaction solution was mixed with HCl aqueous solution (390 mL, concentration 4 mol / L) at 0°C, and ether (360 mL) was added to extract the organic silicon polymer synthesized by the reaction. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) gave 17.3g of liquid organosilicon polymer, with a reaction yield of 75.1%. Gel permeation chromatography analysis showed that the number average molecular weight was 1158 and the weight average molecular weight was 3027.

[0100] Liquid organosilicon polymer (2 g) was mixed with dibenzoyl peroxide (0.02 g) and then cured at 120°C for 1 h in a nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 79.3%. Elemental analysis showed that the C content was 32.31 wt%, the O content was 1.41 wt%, and the Si content was 66.28 wt% by subtraction, and the C / Si ratio was 1.14.

[0101] Example 3

[0102] Under nitrogen protection, magnesium metal (25.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and Cl synthesized in Example 1 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (9.4 g), and kept reacting at 65 °C for 12 h.

[0103] The reaction solution was mixed with HCl aqueous solution (445 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 20.0g of liquid organosilicon polymer with a reaction yield of 86.2%. Gel permeation chromatography analysis showed that the number average molecular weight was 1949 and the weight average molecular weight was 7002.

[0104] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 84.3%. Elemental analysis showed that the C content was 31.78 wt%, the O content was 1.72 wt%, and the Si content was 66.5 wt% by subtraction method, and the C / Si ratio was 1.12.

[0105] Example 4

[0106] Under nitrogen protection, magnesium metal (24.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and Cl 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The temperature of the reaction solution was lowered to room temperature, and then LiAlH 4 (9.6 g), and kept reacting at 65 °C for 12 h.

[0107] The reaction solution was mixed with HCl aqueous solution (430 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 18.9g of liquid organosilicon polymer with a reaction yield of 84.2%. Gel permeation chromatography analysis showed that the number average molecular weight was 1894 and the weight average molecular weight was 7078.

[0108] Take liquid silicone polymer (2g) and tert-butyl perbenzoate (0.02g) and mix them evenly, then keep them at 120℃ for 1h in a nitrogen atmosphere to cure. Then, raise the temperature to 1000℃ at 10℃ / min in a thermogravimetric analyzer, and the mass retention rate is 83.9%. Elemental analysis shows that the C content is 30.52wt%, the O content is 1.70wt%, and the Si content is 67.78wt% by subtraction method, and the C / Si ratio is 1.05. Further pyrolysis to 1600℃, the mass retention rate is 83.1%, and X-ray diffraction is as shown in the attached figure. Figure 3 As shown, it shows typical SiC crystal diffraction peaks.

[0109] Example 5

[0110] Under nitrogen protection, magnesium metal (35.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 0.75 (CH 3 O) 2.25 (43.5 g) and Cl 3CSiCl 0.75 (CH 3 O) 2.25 After the addition of the feed, the reaction was carried out at 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (5.6 g), and reacted at 65 °C for 12 h.

[0111] The reaction solution was mixed with HCl aqueous solution (630 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. Compared with Example 2, the amount of suspended matter in the middle phase increased significantly. The upper organic phase was separated and Na 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa). 14.5g of liquid organosilicon polymer was obtained, and the reaction yield was only 65%. After analyzing the suspended matter in water, its infrared structure was consistent with the obtained liquid organosilicon polymer, and it was speculated to be a highly cross-linked organosilicon polymer. Due to cross-linking, it is difficult to dissolve, thus affecting the reaction yield.

[0112] Example 6

[0113] Under nitrogen protection, magnesium metal (24.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g), Cl 3 CSiCl 1.25 (CH 3 O) 1.75 (24.5g) and allyl chloride (1.52g). After the addition of the materials, the reaction was carried out at 65℃ for 12h. The reaction solution was cooled to room temperature and LiAlH 4 (9.6 g), and kept reacting at 65 °C for 12 h.

[0114] The reaction solution was mixed with HCl aqueous solution (430 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 19.3g of liquid organosilicon polymer with a reaction yield of 86.3%. Gel permeation chromatography analysis showed that the number average molecular weight was 1974 and the weight average molecular weight was 7693.

[0115] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 84.4%. Elemental analysis showed that the C content was 30.54wt%, the O content was 1.63wt%, and the Si content was 67.83wt% by subtraction method, and the C / Si ratio was 1.05.

[0116] Example 7

[0117] Under nitrogen protection, magnesium metal (23.8 g) and tetrahydrofuran (310 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and Cl synthesized in Example 1 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was heated to 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (9.3 g), and reacted at 65 °C for 12 h.

[0118] The reaction solution was mixed with HCl aqueous solution (420 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 19.2g of liquid organosilicon polymer with a reaction yield of 84.0%. Gel permeation chromatography analysis showed that the number average molecular weight was 1730 and the weight average molecular weight was 6932.

[0119] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 h in a nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 84.1%. Elemental analysis showed that the C content was 32.14 wt%, the O content was 1.46 wt%, and the Si content was 66.40 wt% by subtraction, and the C / Si ratio was 1.13.

[0120] Example 8

[0121] Add Cl in one go to a 1000 mL two-necked flask with a dropping funnel and a gas tube. 2 CHSiCl 3 (437 g), then CH 3 OH (112 g), then reacted at room temperature for 2 h, the HCl produced by the reaction was absorbed and neutralized by NaOH aqueous solution to obtain Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 (It is Cl 2 CHSiCl 2 (CH 3 O), Cl 2 CHSiCl(CH 3 O) 2 With Cl 2 CHSi(CH 3 O) 3 The molar ratio of the three components in the formed mixture was estimated by NMR to be approximately 0.33:0.59:0.08).

[0122] Under nitrogen protection, magnesium metal (22.1 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and the Cl synthesized in this example 2 CHSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (10.5 g), and reacted at 65 °C for 12 h.

[0123] The reaction solution was mixed with HCl aqueous solution (390 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 18.2g of liquid organosilicon polymer with a reaction yield of 76.3%. Gel permeation chromatography analysis showed that the number average molecular weight was 1352 and the weight average molecular weight was 4268.

[0124] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 78.4%. Elemental analysis showed that the C content was 32.53 wt%, the O content was 1.66 wt%, and the Si content was 65.81 wt% by subtraction method, and the C / Si ratio was 1.15.

[0125] Example 9

[0126] Under nitrogen protection, magnesium metal (23.8 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g), Cl synthesized in Example 1 3 CSiCl 1.25 (CH 3 O) 1.75 (12.3 g) and Cl synthesized in Example 8 2 CHSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (9.9 g), and reacted at 65 °C for 12 h.

[0127] The reaction solution was mixed with HCl aqueous solution (420 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 18.7g of liquid organosilicon polymer with a reaction yield of 79.1%. Gel permeation chromatography analysis showed that the number average molecular weight was 1539 and the weight average molecular weight was 5397.

[0128] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 80.4%. Elemental analysis showed that the C content was 32.55 wt%, the O content was 1.61 wt%, and the Si content was 65.84 wt% by subtraction method, and the C / Si ratio was 1.15.

[0129] Example 10

[0130] Under nitrogen protection, magnesium metal (28.9 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (35.2 g) and Cl synthesized in Example 8 2 CHSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The temperature of the reaction solution was lowered to room temperature, and then LiAlH 4 (8.0 g), and reacted at 65 °C for 12 h.

[0131] The reaction solution was mixed with HCl aqueous solution (510 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. Compared with Example 8, the amount of suspended matter in the middle phase increased significantly. The upper organic phase was separated and Na 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa). 15.7g of liquid organosilicon polymer was obtained, and the reaction yield was only 67.1%, which was equivalent to Comparative Example 1. After analyzing the suspended matter in water, its infrared structure was consistent with the obtained liquid organosilicon polymer, and it was speculated to be the highly cross-linked organosilicon polymer. Due to the cross-linking, it was difficult to dissolve, thus affecting the reaction yield.

[0132] Embodiment 11

[0133] Under nitrogen protection, magnesium metal (32.3 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, ClCH 2 SiCl 0.75 (CH 3 O) 2.25 (52.2 g) and Cl 3 CSiCl 0.75 (CH 3 O) 2.25 After the addition of the feed, the mixture was kept at 65°C for 12 h. The reaction solution was cooled to room temperature and LiAlH 4 (6.8 g), and reacted at 65 °C for 12 h.

[0134] The reaction solution was mixed with HCl aqueous solution (570 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) gave 17.8g of liquid organosilicon polymer, with a reaction yield of 79%. Gel permeation chromatography analysis showed that the number average molecular weight was 2139 and the weight average molecular weight was 13852.

[0135] Liquid organosilicon polymer (2 g) was mixed with dibenzoyl peroxide (0.02 g) and then cured at 120°C for 1 hour in a nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 88.1%. Elemental analysis showed that the C content was 32.25wt%, the O content was 1.54wt%, and the Si content was 66.21wt% by subtraction method, and the C / Si ratio was 1.14.

[0136] Example 12

[0137] Under nitrogen protection, magnesium metal (27.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (44.0 g) and Cl synthesized in Example 8 2 CHSiCl 1.25 (CH 3 O)1.75 After the addition of the feed, the mixture was kept at 65°C for 12 h. The temperature of the reaction solution was lowered to room temperature, and then LiAlH 4 (8.7 g), and reacted at 65 °C for 12 h.

[0138] The reaction solution was mixed with HCl aqueous solution (480 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) obtained 18.5g of liquid organosilicon polymer with a reaction yield of 78.5%. Gel permeation chromatography analysis showed that the number average molecular weight was 1794 and the weight average molecular weight was 8402.

[0139] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 hour under nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 82.9%. Elemental analysis showed that the C content was 32.60wt%, the O content was 1.40wt%, and the Si content was 66wt% by subtraction method, and the C / Si ratio was 1.15.

[0140] Embodiment 13

[0141] Under nitrogen protection, magnesium metal (27.3 g) and tetrahydrofuran (400 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 60° C. Then, ClCH synthesized in Comparative Example 1 was added in sequence through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (70.5 g) and Cl synthesized in Example 1 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the feed, the mixture was kept at 65°C for 20 h. The temperature of the reaction solution was lowered to room temperature, and then NaAlH 4 (15 g), and reacted at 65 °C for 10 h.

[0142] The reaction solution was mixed with HCl aqueous solution (400 mL, concentration 5 mol / L) at -10°C, and toluene (400 mL) was added to extract the organic silicon polymer synthesized by the reaction. 2 SO4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value -0.093 to -0.096MPa) were performed to obtain 18.9g of liquid organosilicon polymer with a reaction yield of 80%. According to gel permeation chromatography analysis, the number average molecular weight was 1872 and the weight average molecular weight was 7105.

[0143] Liquid organosilicon polymer (2 g) was mixed with tert-butyl peroxybenzoate (0.02 g) and then cured at 120°C for 1 h in a nitrogen atmosphere. The temperature was then raised to 1000°C at 10°C / min in a thermogravimetric analyzer, and the mass retention rate was 84.0%. Elemental analysis showed that the C content was 32.62 wt%, the O content was 1.39 wt%, and the Si content was 65.99 wt% by subtraction, and the C / Si ratio was 1.15.

[0144] Embodiment 14

[0145] Under nitrogen protection, magnesium metal (27.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, a condenser and a dropping funnel, and the temperature was raised to 55°C. Then, the ClCH synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 2 SiCl 1.25 (CH 3 O) 1.75 (61.6 g) and Cl synthesized in Example 1 3 CSiCl 1.25 (CH 3 O) 1.75 After the addition of the materials, the mixture was kept at 65°C for 12 h. Then the mixture was cooled to room temperature and LiAlH 4 (8.6 g) and kept reacting at 65°C for 12 h.

[0146] The reaction solution was mixed with HCl aqueous solution (480 mL, concentration 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. 2 SO 4 Drying and vacuum distillation (maximum distillation temperature 60°C, pressure gauge display value of -0.093 to -0.096MPa) gave 17.8g of liquid organosilicon polymer, with a reaction yield of 83%. Gel permeation chromatography analysis showed that the number average molecular weight was 1963 and the weight average molecular weight was 10314.

[0147] Since there is no unsaturated group, the mass retention rate is 70% when the temperature is increased to 1000°C at 10°C / min in a thermogravimetric analyzer. Elemental analysis shows that the C content is 29.78wt%, the O content is 1.43wt%, and the Si content is 68.79wt% by subtraction method, and the C / Si ratio is 1.01.

[0148] Embodiment 15

[0149] The organic silicon polymer prepared in Example 2 is applied to SiC f Preparation of SiC composite materials.

[0150] The SiC f The / SiC composite material is prepared by the following method:

[0151] CH 4 The carbon source precursor is used, the third-generation two-dimensional SiC fiber cloth is used as the reinforcement, the deposition temperature is 1000°C, the deposition pressure is 5kPa, the deposition time is 5h, and a pyrolytic carbon layer is formed on the surface of the SiC fiber. 9.1g of silicon powder with an average particle size of 50nm, 0.09g of polyvinyl alcohol, 1.0g of tert-butyl peroxybenzoate and 0.05g of tert-butyl catechol are added to 100mL of tetrahydrofuran and ball milled at high speed for 10h. Then 100g of liquid silicone polymer with a C / S ratio of 1.14 prepared in Reference Example 2 is added, stirred evenly, and then the tetrahydrofuran is extracted under reduced pressure. After that, the SiC fiber cloth with a pyrolytic carbon layer deposited on the surface is impregnated, and the fully impregnated SiC fiber cloth is clamped in a graphite fixture, and then pyrolyzed to 1450°C at 2°C / min and kept warm for 1h. Repeat the impregnation and pyrolysis cycle 10 times to obtain SiC f / SiC composite material. The three-point flexural strength at room temperature is 530MPa.

[0152] Example 16

[0153] The organic silicon polymer prepared in Example 2 is applied to SiC f Preparation of SiC composite materials.

[0154] The SiC f The / SiC composite material is prepared by the following method:

[0155] 20g of SiC powder with an average particle size of 40nm, 0.5g of commercially available ZY-DP dispersant from Hunan Zhongyan Building Materials Technology Co., Ltd., and 1.0g of dibenzoyl peroxide were added to 100g of liquid organic silicon polymer with a C / S ratio of 1.14 obtained in Reference Example 2 and stirred evenly. Then, the SiC fiber cloth with a pyrolytic carbon layer deposited on the surface obtained in Reference Example 14 was impregnated, and the fully impregnated SiC fiber cloth was clamped in a graphite fixture, and then pyrolyzed to 1200℃ at 2℃ / min and kept warm for 1h. The impregnation and pyrolysis cycle was repeated 10 times to obtain SiCf / SiC composite material. The three-point flexural strength at room temperature is 670MPa.

[0156] Embodiment 17

[0157] The organic silicon polymer prepared in Example 4 is applied to C f Preparation of SiC composite materials.

[0158] The C f The / SiC composite material is prepared by the following method:

[0159] CH 4 The carbon source precursor was used, C fiber cloth was used as reinforcement, the deposition temperature was 1000°C, the deposition pressure was 5 kPa, the deposition time was 4 h, and a pyrolytic carbon layer was formed on the surface of the C fiber. The C fiber cloth was clamped in a graphite fixture, and then the C fiber cloth was impregnated with a liquid organic silicon polymer with a C / Si ratio of 1.05 synthesized in Example 4, and then the temperature was raised to 1200°C at 2°C / min, and kept at 150°C, 180°C and 1200°C for 1 h respectively. The impregnation and pyrolysis cycle was repeated 10 times to obtain C f / SiC composite material. The three-point flexural strength at room temperature is 490MPa.

[0160] Embodiment 18

[0161] The organosilicon polymer prepared in Example 7 is used in the preparation of porous SiC ceramics.

[0162] The porous SiC ceramic is prepared by the following method:

[0163] To the organosilicon polymer prepared in Example 7, add 60wt% of polyacrylonitrile-acrylamide foamed microspheres from Yizheng Futian Trading Co., Ltd. and 2wt% of tert-butyl perbenzoate, mix well, and place in a 120°C oven for 0.5h. Then, heat to 1200°C at a rate of 5°C / min in a nitrogen atmosphere and keep warm for 1h. After cooling naturally to 800°C, air is introduced and kept warm for 3h. The density of the porous SiC ceramic obtained is 0.33g / cm 3 , porosity is 85.1%; the chemical formula of the ceramic product is SiC 1.06 O 0.10 .

[0164] Embodiment 19

[0165] The organosilicon polymer prepared in Example 7 is used to prepare SiC ceramic protective coating on the surface of carbon fiber.

[0166] The SiC ceramic protective coating on the carbon fiber surface is prepared by the following method:

[0167] The organosilicon polymer prepared in Example 7 was dissolved in tetrahydrofuran to a concentration of 2wt%. Then, dibenzoyl peroxide and N,N-dimethylaniline were added at a mass of 1% of the organosilicon polymer and mixed evenly. The carbon fiber treated at 500°C for 2 hours in a nitrogen atmosphere was immersed in the above solution, then taken out to dry and heated to 1200°C at a rate of 2°C / min in a nitrogen atmosphere and kept warm for 1 hour to obtain a carbon fiber with a SiC protective coating on the surface, as shown in the attached Figure 4 In a thermogravimetric analyzer, the mass retention rate was 89% when the temperature was increased from 10°C / min to 1000°C, while the mass retention rate of pure carbon fiber was only 0.9%.

[0168] By comparing Comparative Example 1 with Example 1, and Comparative Example 2 with Example 2, it can be seen that compared with the monomer ClCH 2 SiCl 1.25 (CH 3 O) 1.75 or ClCH 2 SiCl 0.75 (CH 3 O) 2.25 , monomer Cl 3 CSiCl 1.25 (CH 3 O) 1.75 or Cl 3 CSiCl 0.75 (CH 3 O) 2.25 The introduction of can significantly improve the synthesis yield, molecular weight, ceramic yield and storage period of organosilicon polymers.

[0169] For the organosilicon polymer of the present invention, the content of unsaturated cross-linking groups is crucial. When the content of cross-linking groups is appropriate, it is beneficial to improve the ceramic yield; when the content of cross-linking groups is too low, it will lead to a decrease in the ceramic yield; when the content of cross-linking groups is too high, the ceramic yield will be reduced and the residual carbon content will increase due to the degradation of the cross-linking groups. By comparing Comparative Example 1 and Comparative Example 3, it can be seen that the reduction of unsaturated cross-linking groups will lead to a decrease in the ceramic yield; however, for the present invention (such as the comparison of Example 1, Example 3 and Example 4), due to the high molecular weight of the synthesized organosilicon polymer, although the content of cross-linking groups is reduced, it will not have an adverse effect on the ceramic yield, but will be beneficial to the improvement of the ceramic yield and the reduction of the residual carbon content (C / Si ratio).

[0170] By comparing Example 2, Example 11 and Example 5, it can be seen that when Cl 3 CSiCl 0.75 (CH 3 O) 2.25When the content of silane in the monomer increases from 10% to 40%, the reaction yield, molecular weight and ceramic yield of the obtained liquid silicone polymer are relatively higher than those without Cl 3 CSiCl 0.75 (CH 3 O) 2.25 The monomer of Comparative Example 2 is greatly improved, but when Cl 3 CSiCl 0.75 (CH 3 O) 2.25 When the monomer content is increased to 50%, the reaction yield of the obtained organosilicon polymer is significantly reduced compared with the monomer content of 10% to 40%, and the reduction is close to that of Comparative Example 2, so Cl 3 CSiCl 0.75 (CH 3 O) 2.25 The content should not exceed 50%.

[0171] By comparing Example 4 with Example 6, it can be seen that in the Grignard reaction stage, the monomer Cl 3 CSiCl 1.25 (CH 3 O) 1.75 The feeding time is later than that of ClCH 2 SiCl 1.25 (CH 3 O) 1.75 , which is more conducive to improving the molecular weight, reaction yield and ceramic yield of silicone polymers.

[0172] By comparing Example 1, Example 8 and Example 9, from Example 8 to Example 9 and then to Example 1, the monomer Cl 3 CSiCl 1.25 (CH 3 O) 1.75 The content gradually increases, and the monomer Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 The content gradually decreases, and the molecular weight of the liquid silicone polymer gradually increases. 3 CSiCl 1.25 (CH 3 O) 1.75 The addition of Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 It has better effects of improving molecular weight, yield and ceramic yield.

[0173] By comparing Example 8, Example 12 and Example 10, it can be seen that when Cl 2CHSiCl 1.25 (CH 3 O) 1.75 When the content of silane in the monomer increases from 20% to 50%, the reaction yield, molecular weight and ceramic yield of the obtained liquid organic silicon polymer are relatively higher than those without Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 The monomer of Comparative Example 1 is greatly improved, but when Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 When the monomer content is increased to 60%, the reaction yield of the obtained organosilicon polymer is significantly reduced compared with the monomer content of 20% to 50%, and the reduction is close to that of Comparative Example 1, so Cl 2 CHSiCl 1.25 (CH 3 O) 1.75 The content should not exceed 60%.

[0174] By comparing Comparative Example 4 with Example 14, it can be seen that for the organosilicon polymer without unsaturated groups, Cl 3 CSiCl 1.25 (CH 3 O) 1.75 The introduction of significantly increases the molecular weight of the organosilicon polymer, thereby increasing the ceramic yield.

[0175] It can be seen from Examples 15 to 19 that the organic silicon polymer synthesized by the present invention can be used to prepare SiC f / SiC composite materials, C f / SiC composites, porous SiC foams and SiC coatings, etc.

[0176] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0177] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0178] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. An organosilicon polymer, characterized in that: The organosilicon polymer has a main chain formed by alternating Si atoms and C atoms, wherein the main chain includes a branched structure and / or a cyclic structure; the main chain structure includes -Si-CH2-, and and / or Si atom is independently connected to one or more selected from H, alkyl, aryl, substituted aryl, unsaturated group to form sp 3 Hybridization.

2. An organosilicon polymer, characterized in that: The organosilicon polymer has a main chain formed by alternating Si atoms and C atoms, wherein the main chain includes a branched structure and / or a ring structure; the composition structure of the main chain includes -Si-CH2- and Not included Si atom is independently connected to one or more selected from H, alkyl, aryl, substituted aryl, unsaturated group to form sp 3 Hybridization.

3. An organosilicon polymer according to claim 1 or 2, characterized in that: The Si atom is independently connected to one or more selected from H, unsaturated groups to form sp 3 Hybridization.

4. The organosilicon polymer according to claim 1, characterized in that: When the organosilicon polymer contains -Si-CH2- and When there are two structures, The molar amount of the two structures accounts for 1% to 60% of the total molar amount; when the organosilicon polymer contains -Si-CH2-, Three structures, structure The molar amount of the three structures accounts for 1% to 60% of the total molar amount; when the organosilicon polymer contains -Si-CH2- and When there are two structures, The molar amount accounts for 1% to 50% of the total molar amount of the two structures.

5. The organosilicon polymer according to claim 4, characterized in that: When the organosilicon polymer contains -Si-CH2- and When there are two structures, The molar amount of the two structures accounts for 10% to 50% of the total molar amount; when the organosilicon polymer contains -Si-CH2-, Three structures, structure The molar amount of the three structures accounts for 10% to 50% of the total molar amount; when the organosilicon polymer contains -Si-CH2- and When there are two structures, The molar amount of the two structures accounts for 10% to 40% of the total molar amount.

6. An organic silicon polymer according to any one of claims 1-2, 4-5, characterized in that: The molar ratio of Si atoms connected with unsaturated groups to total Si atoms is 0.01 to 0.

2.

7. A method for preparing an organosilicon polymer, characterized in that: The following steps are involved: by and / or as well as A monomer is prepared through a Grignard reaction step and a reduction reaction step to obtain an organosilicon polymer, wherein X is selected from one or more halogen groups; R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from one or more of H, halogen groups, alkyl groups, alkoxy groups, aryl groups, substituted aryl groups and unsaturated groups; and at least one of R1, R2 and R3 is a halogen group or an alkoxy group.

8. A method for preparing an organosilicon polymer, characterized in that: The following steps are involved: by A monomer is prepared through a Grignard reaction step and a reduction reaction step to obtain an organosilicon polymer, wherein X is selected from one or more halogen groups; R1, R2, R3, R7, R8 and R9 are independently selected from one or more of H, halogen groups, alkyl groups, alkoxy groups, aryl groups, substituted aryl groups and unsaturated groups; and at least one of R1, R2 and R3 is a halogen group or an alkoxy group.

9. The preparation method according to claim 7, characterized in that: R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from one or more of H, halogen, alkoxy and unsaturated groups; at least one of R1, R2 and R3 is halogen or alkoxy.

10. The preparation method according to claim 7, characterized in that: The Grignard reaction steps include: monomer and / or And monomer Magnesium metal undergoes a Grignard reaction in an ether solvent to obtain an intermediate of an organosilicon polymer.

11. The preparation method according to claim 7 or 10, characterized in that: In the Grignard reaction step, the monomer and / or The feeding time is later than 12. The preparation method according to claim 10, characterized in that: The Grignard reaction is carried out at 45-85°C for 1-50 hours.

13. The preparation method according to claim 7, characterized in that: When included When there are two monomers, The molar amount of the two monomers accounts for 1% to 60% of the total molar amount; when it contains When there are three monomers, The molar amount of the three monomers accounts for 1% to 60% of the total molar amount; when it contains When there are two monomers, The molar amount of the two monomers accounts for 1% to 50% of the total molar amount of the two monomers.

14. The preparation method according to claim 13, characterized in that: When included When there are two monomers, The molar amount of the two monomers accounts for 10% to 50% of the total molar amount; when it contains When there are three monomers, The molar amount of the three monomers accounts for 10% to 50% of the total molar amount; when it contains When there are two monomers, The molar amount of the two monomers accounts for 10% to 40% of the total molar amount of the two monomers.

15. The preparation method according to any one of claims 7-10, 12-14, characterized in that: In the Grignard reaction step, unsaturated halogenated hydrocarbon and / or its Grignard reagent are added, and the unsaturated halogenated hydrocarbon includes a CX group, and a C=C group and / or a C≡C group, wherein X is a halogen element.

16. The preparation method according to claim 7 or 8, characterized in that: The reduction reaction step comprises: adding a reducing agent to the product of the Grignard reaction to carry out a reduction reaction.

17. The preparation method according to claim 16, characterized in that: The reduction reaction is carried out at 45-85°C for 1-40h.

18. Use of the organosilicon polymer according to claim 1 or 2 or the organosilicon polymer prepared by the preparation method according to claim 7 or 8, characterized in that: The applications include one or more of the following: a. Applied in the preparation of SiC ceramic matrix composite materials, porous SiC ceramics or SiC fibers, b. Preparation of protective coatings for carbon materials, metals, ceramics or ceramic-based composite materials, c. Applied to filling and / or strengthening of carbon materials, metals, ceramics or ceramic matrix composites, d. Applied to the connection of ceramics or ceramic matrix composite materials, e. Applied to the forming of complex SiC ceramic components.

Citation Information

Patent Citations

  • Ultrasonic radiation preparation method of liquid-state polycarbosilane

    CN109400886A

  • Carbosilane polymer and preparation method thereof

    CN115449080A

  • Liquid polycarbosilane as well as preparation method and application thereof

    CN115678019A

  • Method for producing polycarbosilane

    JP2009286891A